GE_GERICHTE C/8754/2016 vom 20. Juni 2019 - GE Cour de justice (2019)
DIVORCE;COPROPRIÉTÉ;IMMEUBLE;SÉPARATION DE BIENS;OBLIGATION D'ENTRETIEN;CONJOINT | CC.650; CC.20'5.al2; CC.649; CC.125; CC.126.al2